1997
DOI: 10.1091/mbc.8.11.2171
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Molecular Events during Secretory Granule Biogenesis Revealed by Sensitivities to Brefeldin A

Abstract: The biogenesis of peptide hormone secretory granules involves a series of sorting, modification, and trafficking steps that initiate in the trans-Golgi and trans-Golgi network (TGN). To investigate their temporal order and interrelationships, we have developed a pulse-chase protocol that follows the synthesis and packaging of a sulfated hormone, pro-opiomelanocortin (POMC). In AtT-20 cells, sulfate is incorporated into POMC predominantly on N-linked endoglycosidase H-resistant oligosaccharides. Subcellular fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 55 publications
3
70
0
Order By: Relevance
“…In parallel studies, we did not observe precursor release when similar methods were used to monitor processing and release of the precursors of NGF (8) or . Indeed, previous work by others (18,27) has shown that large amounts of the precursors of proteins released by the regulated secretory pathway, such as pro-opiomelanocorticotrophin and pro-renin, are also constitutively released from AtT-20 cells. Although these differences could simply reflect overexpression of pro-BDNF saturating the sorting machinery in the transGolgi network (8), constitutive release of the precursor could also be of biological significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel studies, we did not observe precursor release when similar methods were used to monitor processing and release of the precursors of NGF (8) or . Indeed, previous work by others (18,27) has shown that large amounts of the precursors of proteins released by the regulated secretory pathway, such as pro-opiomelanocorticotrophin and pro-renin, are also constitutively released from AtT-20 cells. Although these differences could simply reflect overexpression of pro-BDNF saturating the sorting machinery in the transGolgi network (8), constitutive release of the precursor could also be of biological significance.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of 28-kDa BDNF Occurs in the ER-To determine where in the cell the 28-kDa form of BDNF is generated, we metabolically labeled vv:pro-BDNF infected cells with [ 35 S]Cys-Met for 3 h in the presence or absence of brefeldin A (BFA, 5 g/ml), a molecule that inhibits anterograde vesicular transport from the ER (18). The cells were analyzed immediately or after a further 2-h chase period without BFA.…”
Section: Pro-bdnf Processing In Vv:bdnf-infected Att-20mentioning
confidence: 99%
“…For example, the processing of proinsulin begins in immature secretory granules in ␤-cells (26). Also, the generation of ACTH and ␤-endorphin from the larger precursor proopiomelanocortin (POMC) in AtT-20 cells is predominantly a post-TGN event (27,28), although POMC processing may be initiated in the TGN (29 -31).…”
mentioning
confidence: 99%
“…3A); we observed increased secretion of intact POMC (Fig. 3B), possibly via increased constitutive secretion (Fernandez et al 1997).…”
Section: In Trans Expression Of Pc1 Propeptide Inhibits Pc1-mediated mentioning
confidence: 51%